2021
DOI: 10.1088/1755-1315/679/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Morphological profile of L2 Anisakis typica on Indian Mackerel (Rastrelliger kanagurta) from Sedati Fish Auction, Sidoarjo-East Java, Indonesia using Scanning Electron Microscope (SEM)

Abstract: The aim of this research was to determine Anisakis species that infected Indian mackerel fish in Fish Auction Sedati, Sidoarjo-East Java, Indonesia based on morphometric observation using a binocular microscope and morphological profile using SEM. This study was done on February-March 2019 with 30 Indian mackerel (Rastrelliger kanagurta) were collected from Fish Auction Sedati, Sidoarjo and examined for Anisakis. Anisakis that collected, observed using a binocular microscope and SEM. The result showed there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In our investigation, molecular analysis using ITS and COII revealed that 17 Anisakis samples from Indian mackerels captured in Thailand are A. typica (Diesing, 1860, Nematoda: Anisakidae), also documented in several surveillances of Indian mackerels caught in Indonesia [ 30 , 31 ]. These findings may indicate that Indian mackerels are an important intermediate host of this parasite in Southeast Asia.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In our investigation, molecular analysis using ITS and COII revealed that 17 Anisakis samples from Indian mackerels captured in Thailand are A. typica (Diesing, 1860, Nematoda: Anisakidae), also documented in several surveillances of Indian mackerels caught in Indonesia [ 30 , 31 ]. These findings may indicate that Indian mackerels are an important intermediate host of this parasite in Southeast Asia.…”
Section: Discussionmentioning
confidence: 55%
“…In several countries of Southeast Asia such as Indonesia, Malaysia, Myanmar, and Thailand, they are an economically important marine fish [ 27 , 28 ]. In the past, the Anisakis parasite was found in Indian mackerel in some countries, including China [ 29 ], Indonesia [ 30 , 31 ], and Malaysia [ 32 ] but has never been reported in Thailand. However, our latest study detected Anisakis infections in Indian mackerel fish from the Samut Songkhram fish market [ 15 ].…”
Section: Discussionmentioning
confidence: 99%